Understanding and learning from rural drug service adaptations to opioid substitution therapy during the COVID-19 pandemic: the What C-OST? study - Scott, Jenny; Family, Hannah; Kesten, Joanna May; Hines, Lindsey; Millar, Josie (Frontiers in Public Health, 2023)
This is a provisional file, not the final typeset articleThree overarching themes were found. 'Challenges of rural lockdown' (theme 1) describes how rural community challenges, especially reduced or no rural public transport, were experienced. This hampered some OST collections, with consequential drug use. It also impeded connections to loved ones, worsening isolation. For participants who were struggling pre-pandemic, the intersection between this and their experience of revised drug service operations, is embodied in 'Amplification of Social Disconnection: Cut off and unheard' (theme 2). They felt a lack of support, particularly from remote provision key working. For participants who had supportive relationships and time in the pandemic occupied in ways they found meaningful, and others who struggled with anxiety or depression, found pandemic changes Fits better with my life' (theme 3). They experienced more freedom for other things, gaining support by other means, such as family, or felt more comfortable with remote engagement. A cross cutting sub-theme 'Understandable Interruptions' showed acceptance of pandemic disruptions.National guidance and organizational policy impacted on participants in different ways. Those who had supportive relationships and occupied time were better able to make positive use of newfound freedoms, and engage with community level support. In contrast, those who had less stability, including mental health struggles and social isolation, felt cut off and unheard, particularly from key workers. Reduced rural transport was a significant community-level issue, which impeded OST collection and social support. We suggest emergency response plans be created for individuals taking account of their pre-existing personal situations.